Paso Robles Community Hospital #1 and #2 - Southern Pacific Milling Company::::::::: (1938)
#1: 'Vine Street plot plan, door schedule, window schedule, framing details, foundation plan, floor plan.' #2: 'North Elevation, south wall, south elevation, north wall, west wall, south wall, east wall, west elevation, int. door frame, exterior door frame, jamb, window frame, detail of base, ceiling treatment for maternity room and nursery.'